SPECIFIC ASPECTS OF IMPROVING HOUSEHOLD FINANCES - Khojiyev Jakhongir Dushabayevich (Scholar Express Journals, 2022)
In the article, the current state of financial relations in households, the issues of increasing the income of the population, overcoming poverty and ensuring economic growth in our country are studied through analysis. Attention is also paid to the issues of ensuring the financial stability of households in our country. This article examines the use of household funds for the purchase of goods, the payment of taxes and mandatory payments, the purchase of housing and other purposes, as well as the use of excess income for post-saving
Keywords: Households; household finances; population income; decile coefficient